2018
DOI: 10.1038/s41437-018-0099-5
|View full text |Cite
|
Sign up to set email alerts
|

A new genomic prediction method with additive-dominance effects in the least-squares framework

Abstract: In our previous work, we proposed a genomic prediction method combing identical-by-state-based Haseman-Elston regression and best linear prediction with additive variance component only (HEBLP|A herein), the most essential component of genetic variation. Since the dominance effects contribute significantly in heterosis, it is desirable to incorporate the HEBLP with dominance variance component that is expected to enhance the predictive accuracy as we move to the further development: HEBLP|AD, a paralleled impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In other conditions, both methods performed similarly (for example, when a training population size was 20,000 r 2 GBLUP = 0:653 ± 0:017 vs. r 2 RHEPCG = 0:648 ± 0:021). With the enlargement of the training population, the predictive accuracy approximated the true heritability, which as some studies have demonstrated, is the upper bound of predictive accuracy (de los Campos et al, 2013;Liu and Chen, 2018). Meanwhile, RHEPCG was significantly faster than GBLUP (for example, when a training population size was 20,000 T GBLUP =53666s vs T RHEPCG =1237s ).…”
Section: Resultsmentioning
confidence: 85%
“…In other conditions, both methods performed similarly (for example, when a training population size was 20,000 r 2 GBLUP = 0:653 ± 0:017 vs. r 2 RHEPCG = 0:648 ± 0:021). With the enlargement of the training population, the predictive accuracy approximated the true heritability, which as some studies have demonstrated, is the upper bound of predictive accuracy (de los Campos et al, 2013;Liu and Chen, 2018). Meanwhile, RHEPCG was significantly faster than GBLUP (for example, when a training population size was 20,000 T GBLUP =53666s vs T RHEPCG =1237s ).…”
Section: Resultsmentioning
confidence: 85%
“…Dominance effects include incomplete dominance, complete dominance and overdominance, and these effects vary for different traits. Typical genomic prediction models with dominance genetic effects assume that dominance genetic effects of all loci have the same variance and directly use genomic markers to construct a dominance genetic relationship matrix between individuals using the same matrix for all traits (Alves et al 2020 ; Liu and Chen 2018 ; Su et al 2012 ). In the present study, the SNP loci are weighted according to the degree of deviation between heterozygous and homozygous loci, which differentiates the degrees of dominance effects on the trait between loci.…”
Section: Discussionmentioning
confidence: 99%
“…Nonadditive variance, which includes dominance and epistatic effects that generally consist of various interaction effects, such as AA, additive-by-dominance (AD), and dominance-by-dominance (DD) interaction effects, has long been recognized as essential component for dissecting the genetic architecture of target traits and understanding the genetic basis of quantitative traits (Su et al, 2012; Da et al, 2014; Muñoz et al, 2014; Azevedo et al, 2015; Jiang and Reif, 2015; Zhao et al, 2015; Bouvet et al, 2016; Dias et al, 2018; Liu and Chen, 2018; Varona et al, 2018). Several studies were performed using TRMs to test the effect of various combinations of nonadditive effects in extended GBLUP models.…”
Section: Discussionmentioning
confidence: 99%